Social Perception of Risk and Protection Factors for the Children of Emigrant Mothers: A Study in the Dominican Republic - Uriarte Arcinie, Juan de Dios (Migraciones Internacionales, 2017)
Th e feminization of work-related migration alters family roles and relationships and has a direct impact on the development of the children left behind. The purpose of this study is to show the risk and protection factors perceived in Dominican society for children when the mother emigrates. Risk factors include a lack of mother-child communication; being demanding in relationships; and an anomalous substitute family atmosphere. Conversely, protection factors encompass frequent communication with the mother; an aff ectionate relationship between the guardian and the child; when the guardian is a family member who is very close to the mother and the promotion of values such as thrift, eff ort and sacrifice. The results of social perception coincide with existing literature, but it is debatable whether the factors perceived are actually those that most aff ect the psychological and social development of children left behind by migration. Percepción social de factores de riesgo y de protección para los hijos de madres emigrantes: Un estudio en la República Dominicana Resumen La feminización de la migración laboral altera los roles y relaciones familiares e impacta en el desarrollo de los niños que quedan en el lugar de origen. El objetivo del estudio es mostrar los factores de riesgo y de protección percibidos en la sociedad dominicana para los hijos cuando emigra la madre. Como factores de riesgo destacan: la falta de comunicaciones entre madre e hijo; ser exigente en las relaciones; y el ambiente familiar sustituto anómalo. En cambio, son factores de protección: la comunicación frecuente con la madre y las relaciones afectuosas entre la tutora y el hijo. Cuando ésta es un familiar muy cercano a la madre, fomenta valores como el ahorro, el esfuerzo y el sacrificio. Los resultados de la percepción social coinciden con la literatura existente, pero se discute si los factores percibidos son los que más afectan el desarrollo psicosocial de los niños que quedan atrás por la migración.